Downcast eyes : the denigration of vision in twentieth-century French thought - Jay, Martin, 1944- (University of California Press, 1993)
Long considered "the noblest of the senses," vision has increasingly come under critical scrutiny by a wide range of thinkers who question its dominance in Western culture. These critics, especially prominent in twentieth-century France, have challenged vision's allegedly superior capacity to provide access to the world. They have also criticized its supposed complicity with political and social oppression through the promulgation of spectacle and surveillance. Martin Jay turns to this antiocularcentric discourse and explores its often contradictory implications in the work of such influential figures as Jean-Paul Sartre, Maurice Merleau-Ponty, Michel Foucault, Jacques Lacan, Louis Althusser, Guy Debord, Luce Irigaray, Emmanuel Levinas, and Jacques Derrida. Jay begins with a discussion of the theory of vision from Plato to Descartes, then considers vision's role in the French Enlightenment before turning to its status in the culture of modernity. From French Impressionism to Georges Bataille and the Surrealists, Roland Barthes's writings on photography, and the film theory of Christian Metz, Jay provides lucid and fair-minded analyses of thinkers and ideas widely known for their difficulty. His book examines the myriad links between the interrogation of vision and the pervasive antihumanist, antimodernist, and counter-enlightenment tenor of much recent French thought. Refusing, however, to defend the dominant visual order, he calls instead for a plurality of "scopic regimes." Certain to generate controversy and discussion throughout the humanities and social sciences, Downcast Eyes will consolidate Jay's reputation as one of today's premier cultural and intellectual historians
"A Centennial book"--P. [ii].
Keywords: Vision.; Cognition and culture.; Philosophy, French -- 20th century.; France -- Civilization -- 20th century.; France -- Intellectual life -- 20th century.; Philosophy.; Culture.; Vision, Ocular; Philosophy; Culture; Cognition et culture.; Philosophie française -- 20e siècle.; France -- Civilisation -- 20e siècle.; France -- Vie intellectuelle -- 20e siècle.; Philosophie.; sight (sense); philosophy.; culture note.; culture (concept); PHILOSOPHY -- History & Surveys -- Modern.; PHILOSOPHY -- Political.; Civilization; Cognition and culture; Intellectual life; Philosophy, French; Vision; France; Philosophie; Sehen; Frankreich; Visuele waarneming.; Filosofische aspecten.; Frankrijk.; Filosofia contemporanea.; Esthétique -- France -- 20e siècle.; Philosophie et littérature.; Phénoménologie et littérature.; Perception visuelle -- Philosophie.; Philosophie -- France -- 20e siècle.; 1900-1999; Geschichte 1900-1990.